The Influence of Product Quality, Price, Brand Image, E WoM and WoM on Purchase Decisions - Hary Sulaksono; Mohd Farid Shamsudin; Tamriatin Hidayah (LPPM Institut Teknologi dan Sains Mandala, 2022)
This study aims to analyze the effect of product quality, price, brand image, E WoM and WoM on purchasing decisions for Oriflame products. Case studies at SPO Amalia Kartika Putri Situbondo.This type of research is included in the type of quantitative research.The sample used was 40 respondents with a purposive sampling technique. The data analysis method used is Multiple Linear Regression analysis.the influence of WoM on Purchase Decision shows that there is a positive and significant influence. Purchases show no negative and significant influence. the effect of Price on Purchase Decision shows that there is a positive and significant influence; Brand Image on Purchasing Decisions shows a positive and significant influence; E-WOM on Purchase Decision shows a positive and significant influence; the influence of WOM on Purchase Decision shows that there is a positive and significant influence. the influence of Product Quality, Price, Brand Image, E-WOM, and WOM shows that there is a positive and significant influence.